Campus snobs - Bertram, Moira (Sydney : Calvert, 1956)
Romance.
Cover title.
Distributed by Gordon & Gotch (A'sia) Ltd. Sydney, Melbourne.
Moira Bertram was one of the few women working in Australian comics in the 1940s and 1950s. She ended her comic book career in the late 1950s.
Keywords: Australian; Comic books, strips, etc